Parents and whānau as experts in their worlds: valuing family pedagogies in early childhood. (3rd July 2021) - Jacobs, Mary M.; Harvey, Nola; White, Amanda
ABSTRACT: Growing tension within the early childhood education sector of Aotearoa New Zealand around the roles teachers and families might play in preparing children for success in school suggests that notions of readiness are gaining traction. In this paper, we draw on data from three empirical studies to position families as experts in the lives of their children, valuing the linguistically and culturally diverse literacies children carry from their whānau, homes, and communities in bicultural and superdiverse Aotearoa New Zealand. Exemplars of family pedagogies framed through a funds of knowledge theoretical lens, provide counternarratives to deficit discourses regarding children's language competencies, and challenge the encroaching reductionist notion of the 'language gap' and narrow views of early literacy promoted in the preparation of children for English-medium schooling. The data presented highlight family linguistic and cultural resources, the efforts of families to sustain home languages, and the critical role of early childhood teachers to engage in reciprocal partnerships with families. Affirmation of the complexities of children's language/s and literacies and the work of early childhood teachers are discussed in the implications for early childhood teacher education and professional development, centre leadership, and policy.